Sprawozdanie z "17. Warsztatów Filozofii Przyrody" Sekcji Filozofii Przyrody i Nauk Przyrodniczych Polskiego Towarzystwa Filozoficznego, Kraków, 13-16.06.2024 r. - Jakub Płoski; Milena Żydek (Studia Philosophiae Christianae)
On June 13-16th, 2024, the 17th Natural Philosophy Workshop was held at the Hampton by Hilton hotel in Kraków. Together with the permanent organizer, the Section of the Philosophy of Nature and Natural Sciences of the Polish Philosophical Society, this year’s edition of the workshop was co-organized by the En Arche Foundation. The event program included lectures, a scientific debate and a graduate student poster competition. The workshop participants included representatives of scientific centers engaged in the philosophy of nature and natural sciences from Kraków, Lublin, Łódź, Poznań, Szczecin, Toruń, Warsaw, Zielona Góra and Akron (USA).